Why Do People Keep Their Promises? An Experimental Test of Two Explanations - Vanberg, Christoph (Econometrica, 2008)
Numerous psychological and economic experiments have shown that the exchange of promises greatly enhances cooperative behavior in experimental games. This paper seeks to test two theories to explain this effect. The first posits that individuals have a preference for keeping their word. The second assumes that people dislike letting down others' payoff expectations. According to the latter account, promises affect behavior only indirectly, because they lead to changes in the payoff expectations attributed to others. I conduct an experiment designed to distinguish between and test these alternative explanations. The results demonstrate that the effects of promises cannot be accounted for by changes in payoff expectations. This suggests that people have a preference for promise keeping per se.